2010
DOI: 10.1128/jvi.02620-08
|View full text |Cite
|
Sign up to set email alerts
|

Poly(A) at the 3′ End of Positive-Strand RNA and VPg-Linked Poly(U) at the 5′ End of Negative-Strand RNA Are Reciprocal Templates during Replication of Poliovirus RNA

Abstract: A 3 poly(A) tail is a common feature of picornavirus RNA genomes and the RNA genomes of many other positive-strand RNA viruses. We examined the manner in which the homopolymeric poly(A) and poly(U) portions of poliovirus (PV) positive-and negative-strand RNAs were used as reciprocal templates during RNA replication. Poly(A) sequences at the 3 end of viral positive-strand RNA were transcribed into VPg-linked poly(U) products at the 5 end of negative-strand RNA during PV RNA replication. Subsequently, VPg-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 49 publications
3
53
0
Order By: Relevance
“…We found that alanine substitution mutations within phylogenetically conserved regions of 3D pol resulted in populations of virion RNA with altered poly(A) tail lengths, consistent with the predicted reiterative transcription mechanisms of viral RNA replication (8). Data from reaction mixtures containing purified 3D pol confirmed that 3D pol mutations influenced the amounts of reiterative transcription on a defined poly(U) template.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…We found that alanine substitution mutations within phylogenetically conserved regions of 3D pol resulted in populations of virion RNA with altered poly(A) tail lengths, consistent with the predicted reiterative transcription mechanisms of viral RNA replication (8). Data from reaction mixtures containing purified 3D pol confirmed that 3D pol mutations influenced the amounts of reiterative transcription on a defined poly(U) template.…”
supporting
confidence: 50%
“…Poliovirus type 1 (Mahoney) was used for this study. Poliovirus cDNA clones with genetically encoded poly(A) tails 32, 51, and 84 bases in length were previously described (8). 3D pol muta-tions were introduced into a subgenomic cDNA clone with a poly (A) tail of 84 bases [pRNA2 poly A (84) ] by site-directed mutagenesis (QuikChange XL-II site-directed mutagenesis kit; Stratagene, Inc.) and verified by sequencing the 3CD genes (nucleotides 5438 to 7440).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations